Natural variation and CRISPR/Cas9‐mediated mutation in GmPRR37 affect photoperiodic flowering and contribute to regional adaptation of soybean. Issue 9 (13th February 2020) - Wang, Liwei; Sun, Shi; Wu, Tingting; Liu, Luping; Sun, Xuegang; Cai, Yupeng; Li, Jicun; Jia, Hongchang; Yuan, Shan; Chen, Li; Jiang, Bingjun; Wu, Cunxiang; et al.
Summary: Flowering time is a critical determinant of the geographic distribution and regional adaptability of soybean ( Glycine max ) and is strongly regulated by photoperiod and temperature. In this study, quantitative trait locus (QTL) mapping and subsequent candidate gene analysis revealed that GmPRR37, encoding a pseudo‐response regulator protein, is responsible for the major QTL qFT12‐2, which was identified from a population of 308 recombinant inbred lines (RILs) derived from a cross between a very late‐flowering soybean cultivar, 'Zigongdongdou (ZGDD)', and an extremely early‐flowering cultivar, 'Heihe27 (HH27)', in multiple environments. Comparative analysis of parental sequencing data confirmed that HH27 contains a non‐sense mutation that causes the loss of the CCT domain in the GmPRR37 protein. CRISPR/Cas9‐induced Gmprr37 ‐ZGDD mutants in soybean exhibited early flowering under natural long‐day (NLD) conditions. Overexpression of GmPRR37 significantly delayed the flowering of transgenic soybean plants compared with wild‐type under long photoperiod conditions. In addition, both the knockout and overexpression of GmPRR37 in soybean showed no significant phenotypic alterations in flowering time under short‐day (SD) conditions. Furthermore, GmPRR37 down‐regulated the expression of the flowering‐promoting FT homologues GmFT2a and GmFT5a, and up‐regulated flowering‐inhibiting FT homologue GmFT1a expression under long‐day (LD) conditions. We analysed haplotypes of GmPRR37 among 180 cultivars collected across China and found natural Gmprr37 mutants flower earlier and enable soybean to be cultivated at higher latitudes. This study demonstrates that GmPRR37 controls soybean photoperiodic flowering and provides opportunities to breed optimized cultivars with adaptation to specific regions and farming systems.